THE EFFECTIVENESS OF CASH SOCIAL ASSISTANCE PROGRAM FOR MANAGING ECONOMIC PROBLEMS AFFECTED COMMUNITIES OF COVID-19 IN TIGARAKSA SUB-DISTRICT, TANGERANG REGENCY - Toddy Aditya; Silva Alfiati Himawan; Hendriyanto Hendriyanto; Abdul Khoir (DIA: Jurnal Administrasi Publik, 2022)
The purpose of this study was to determine the Effectiveness of the Cash Social Assistance Program on Overcoming the Economic Problems of Communities affected by Covid-19 in Tigaraksa District. The problem in providing BST in Tigaraksa District is to discuss the effectiveness of cash social assistance in helping people affected by COVID-19, especially on community economic problems. The method used by the researcher is a quantitative method with descriptive research type, with a sample of 386 taken using random sampling of the community in Tigaraksa District. The results showed that the effectiveness of the cash social assistance program scored 69.4%. This shows that the effectiveness of the cash social assistance program in Tigaraksa District is in the good category. overcoming economic problems got a score of 78.8%. This shows that overcoming economic problems in Tigaraksa District is included in the good category and there is a significant effect of the effectiveness of cash social assistance programs on overcoming economic problems, with the magnitude of the effect given by the effectiveness of cash social assistance programs on variables of overcoming economic problems in Tigaraksa District of 90, 4%.